Effect of adipose-derived stem cells-conditioned medium extracellular vesicles on senescent fibroblast and E2F1 expression - Ayuningtyas, Vidya Hana Dwi; Prawitasari, Suci; Rofiq, Aunur; Murlistyarini, Sinta (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Adipose-derived stem cells (ADSCs) are well-known for their regenerative properties, especially towards senescent cells. Extracellular vesicles derived from ADSCs are believed to influence the expression level of the E2 promoter binding factor (E2F1) protein, one of the key proteins regulating the cell cycle. This study aimed to investigate the impact of extracellular vesicles from ADSC-conditioned medium (ADSC-CM) on E2F1 levels and their potential to improve aging cells. METHODS Extracellular vesicles from ADSC-CM were introduced into senescent fibroblasts through transfection. Then, the E2F1 protein levels were measured and compared between transfected and untransfected cells. A total of 18 samples were calculated based on Federer’s formulas. E2F1 protein levels were counted using a cell-based enzyme-linked immunosorbent assay. Senescence-associated beta-galactosidase staining was used to quantify the number of senescent cells in each group, and the microculture tetrazolium technique assay was used to assess cellular metabolic activity. RESULTS The number of senescent cells was lower in the transfected group compared to the untransfected group. ADSC-CM extracellular vesicles-transfected fibroblasts exhibited higher levels of E2F1 protein (0.19 [0.17] ng/ml) compared to untransfected fibroblast (0.06 [0.049] ng/ml; p = 0.048). Higher E2F1 protein levels were associated with reduced senescent fibroblasts and increased metabolic viable fibroblasts in the transfected group. CONCLUSIONS ADSC-CM extracellular vesicles positively affected senescent cells by enhancing the level of E2F1.